2011
DOI: 10.1007/s13593-011-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of crop cultivars by honeycomb breeding

Abstract: The ability of agriculture to adapt to environmental changes and to address main issues of food quality and environment protection is a fundamental factor in achieving sustainability. Low yield capacity of contemporary sustainable farming systems, however, is a major obstacle to future growth of sustainable agriculture. In addition, increasing pressure is placed for higher food supply due to the projected population increase. To overcome these barriers and stimulate the wide adoption of sustainable agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(99 citation statements)
references
References 85 publications
2
78
0
14
Order By: Relevance
“…At the lowest density, more likely to approximate absence of competition, apart from the highest yield, the difference between the two kinds of germplasm was also the greatest. This is in agreement with previous reports showing that the absence of competition maximizes phenotypic expression and differentiation (Fasoula, 1990;Fasoula & Fasoula, 1997, 2000Tokatlidis et al, 2010;Fasoula & Tokatlidis, 2012). Kotzamanidis et al (2009) also reported the highest grain yield per plant in barley at the lowest density (1.15 plants m -2 ).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…At the lowest density, more likely to approximate absence of competition, apart from the highest yield, the difference between the two kinds of germplasm was also the greatest. This is in agreement with previous reports showing that the absence of competition maximizes phenotypic expression and differentiation (Fasoula, 1990;Fasoula & Fasoula, 1997, 2000Tokatlidis et al, 2010;Fasoula & Tokatlidis, 2012). Kotzamanidis et al (2009) also reported the highest grain yield per plant in barley at the lowest density (1.15 plants m -2 ).…”
Section: Introductionsupporting
confidence: 92%
“…However, the yielding ability of a genotype is controlled by different genes than its competitive ability and the two characters are negatively correlated (Fasoula, 1990;Fasoula & Fasoula, 1997, 2002Janick, 1999;Pan et al, 2003;Fasoula & Tokatlidis, 2012). Hence, the capacity of a particular genotype to yield highly may be masked when the population is evaluated under competition conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available relevant investigations are encouraging, while the recently proposed criteria promise greater success. Apart from a number of studies which are supportive of the method in maize and other crops (Fasoula and Tokatlidis 2012), regarding the recently suggested equations, Vlachostergios et al (2011) found that PCYP was an effective selection tool for organic breeding in lentils while Papadopoulos and Tokatlidis (2011) qualified the ECYP as a stability criterion in dry beans and classified it according to the agronomic concept of stability, i.e., to designate cultivars performance in accordance with the available inputs. Fig.…”
Section: Development Of Population-neutral Hybridsmentioning
confidence: 99%
“…Tokatlidis et al (2001) opened the possibility of obtaining such hybrids through honeycomb breeding targeted directly at plant yield potential (Tokatlidis et al 1998). Advanced selection criteria were suggested by Fasoula and Tokatlidis (2012) to create new cultivars with the potential to exploit effectively even marginal environments and meet the needs of sustainable agricultural systems. They speculated that since the method places particular emphasis on selection at ultra-low population to counteract the disturbing effects of plant-to-plant inference in equal share of inputs, it substantially improves plant yield potential, thereby expanding the lower limit of the OP.…”
Section: Development Of Population-neutral Hybridsmentioning
confidence: 99%